Developing Students' Technological Thinking by Means of Sports and Physical Education Activity - S. A. Novoselov; Y. V. Tchub (Russian State Vocational Pedagogical University, 2015)
The new context competence system of vocational training requires the system-creating interdisciplinary link. However, the lack of such interrelation between the humanities, social, economic disciplines and professional subjects badly affects the training results. The quality of training process can be improved by introducing the interdisciplinary principle. In this regard, the authors carried out the research aimed at solving the above problem by developing the method of interdisciplinary correlation and analyzing its system-creating basis.The paper substantiates the possibility of developing students' technological thinking by means of sports and physical education activity corresponding to a particular professional one according to the universal morphology classification. It is demonstrated that technological thinking can be developed in the context of sports games under several organizational and methodical conditions. One of the proposed conditions concerns the project of a sport game improvement. The given method can find its application in designing the training process related to physical education of students of different profiles.